Effects of surface structure deformation on static friction at fractal interfaces. Issue 2 (3rd June 2013) - Hanaor, D. A. H.; Gan, Y.; Einav, I.
Abstract : The evolution of fractal surface structures with flattening of asperities was investigated using isotropically roughened aluminium surfaces loaded in compression. It was found that asperity amplitude, mean roughness and fractal dimension decrease through increased compressive stress and number of loading events. Of the samples tested, surfaces subjected to an increased number of loading events exhibited the most significant surface deformation and were observed to exhibit higher levels of static friction at an interface with a single-crystal flat quartz substrate. This suggests that the frequency of grain reorganisation events in geomaterials plays an important role in the development of intergranular friction. Fractal surfaces were numerically modelled using Weierstrass–Mandelbrot-based functions. From the study of frictional interactions with rigid flat opposing surfaces it was apparent that the effect of surface fractal dimension is more significant with increasing dominance of adhesive mechanisms.